2002
DOI: 10.1159/000067184
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Ulcer Disease and Neuroticism in the United States Adult Population

Abstract: Background: The goal of the current study was to determine the association between personality factors and peptic ulcer disease (PUD) among adults in the general population. Method: Data were drawn from the Midlife Development in the United States Survey (MIDUS), a representative household survey of the adult population (ages 25–74; n = 3,032) of the United States. Multiple logistic regression analyses were used to determine the association between the big five personality factors and PUD, adjusting for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…Our finding also supports research reporting the prognostic importance of depressive symptoms: Depressive symptoms were predictive of similar symptoms 32 years later (Zonderman et al 1993) and similar results are reported by Westermeyer (1998). In contrast, our results do not support findings from studies reporting that personality traits are distinct predictors of objective health (Glazer et al 2002;Goodwin and Stein 2003;Goodwin and Friedman 2006), although it has been criticized that some associations between neuroticism and health result from reporting artefacts (Watson and Pennebaker 1989). On the other hand, our findings confirm results from other prospective studies questioning the over-rated role of openness and emotional reactivity as long-term predictors for adaptation and health in old age (Friedman 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Our finding also supports research reporting the prognostic importance of depressive symptoms: Depressive symptoms were predictive of similar symptoms 32 years later (Zonderman et al 1993) and similar results are reported by Westermeyer (1998). In contrast, our results do not support findings from studies reporting that personality traits are distinct predictors of objective health (Glazer et al 2002;Goodwin and Stein 2003;Goodwin and Friedman 2006), although it has been criticized that some associations between neuroticism and health result from reporting artefacts (Watson and Pennebaker 1989). On the other hand, our findings confirm results from other prospective studies questioning the over-rated role of openness and emotional reactivity as long-term predictors for adaptation and health in old age (Friedman 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Marital Status: Married Divorced/separated/widowed Never married 455 (79) 75 (13) 46 (8) 2643 (73) 681 (19) 305 (8) .003…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies show that personality traits are important risk factors for many psychiatric and non-psychiatric disorders (1)(2)(3)(4)(5)(6)(7)(8)(9). Personality traits are thought to be complex and determined largely by genetic factors (10).…”
Section: Introductionmentioning
confidence: 99%